Character Education and the Challenges of Globalization: A Case Study on Generation Z Students - Niskaromah; Sayida Khoiratun Nisak; Nachima Bakoh; Eko Fabianto (Zabags International Journal of Education, 2025)
This study aims to describe the implementation of character education among Generation Z, analyze the challenges of globalization that influence their character development, and formulate strategies for strengthening character education in the digital era. As digital natives, Generation Z faces both opportunities and risks from the flow of technology, information, and global culture, which may weaken identity and local values if not balanced by strong character education. This research employed a qualitative descriptive case study approach. Primary data were collected through interviews, observations, and documentation, while secondary data were obtained from curriculum documents and related literature. Data were analyzed with triangulation of sources and techniques to ensure validity. The findings reveal four main points: schools have integrated character education into their curricula and activities, globalization and digital culture pose significant challenges, a gap exists between moral knowledge and students’ actions, and strategies remain focused on religious and academic aspects with limited emphasis on local cultural values. The study concludes that character education for Generation Z requires innovative, contextual, and collaborative strategies that integrate technology, local values, and religious principles.